2000
DOI: 10.1007/pl00001981
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Patients with Acute Myocardial Infarction for Primary or Acute Angioplasty from Hospitals without the Facilities to Perform Angioplasty Results from the Pooled Data of the Maximal Individual Therapy in Acute Myocardial Infarction (MITRA) Registry and the Myocardial Infarction Registry (MIR)

Abstract: In patients with acute myocardial infarction (AMI) admitted at hospitals without angioplasty facilities there are some subgroups of patients which seem to profit from a transfer to primary or acute angioplasty. However, current clinical practice at such hospitals is unknown. We analyzed the pooled data of the German acute myocardial infarction registries MITRA and the MIR. Angioplasty was not available at 221/271 hospitals (81.5%). Out of 14,487 patients with acute myocardial infarction admitted to these hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
1
7

Year Published

2001
2001
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 28 publications
4
17
1
7
Order By: Relevance
“…Likewise, in the Global Registry of Acute Coronary Events (39), only 70% of eligible STEMI patients received reperfusion therapy. While the use of primary angioplasty in our study was low when compared with international standards (40,41), the rates of primary angioplasty were comparable with other jurisdictions within Canada (19,42).…”
Section: Discussionsupporting
confidence: 58%
“…Likewise, in the Global Registry of Acute Coronary Events (39), only 70% of eligible STEMI patients received reperfusion therapy. While the use of primary angioplasty in our study was low when compared with international standards (40,41), the rates of primary angioplasty were comparable with other jurisdictions within Canada (19,42).…”
Section: Discussionsupporting
confidence: 58%
“…Third, the difference in the in-hospital case-fatality rate was insignificant between patients who underwent primary PTCA and those who did not, if they were admitted or transferred 24 h or more after symptom onset. Many investigators have reported the advantages of current therapies, including primary PTCA, 2,7,22,23,26 and the in-hospital case-fatality rate of the present study was consistent with those reports (Fig 9).…”
Section: Outcome Of Ptca On the In-hospital Case-fatality Ratesupporting
confidence: 92%
“…The two treatments have not significant differences in terms of complications. There are studies that have reported complications of PPCI are less than thrombolytic, but the number of patients in these studies was higher, and the mean age of the patients in therapy groups for these research is variable [8]. The mortality in both groups was 7.3% and entirely was close to credible other studies [9].…”
Section: Discussionmentioning
confidence: 48%